Analysis of the Influence of Pre-Pregnancy BMI and Weight Gain during Pregnancy on the Weight of Healthy Children during the First 2 Years of Life: A Prospective Study - Beata Łoniewska; Kaja Michalczyk; Konrad Podsiadło; Karolina Adamek; Barbara Michalczyk; Piotr Tousty; Mariusz Kaczmarczyk; Igor Łoniewski (MDPI AG, 2022)
Background: Increased pre-pregnancy maternal BMI (pBMI) and gestational weight gain (GWG) have been found to increase infants' birthweight and result in the programming of child weight and impact its later weight gain. Aim: To assess the impact of pBMI and GWG on the weight of children from birth to 2 years of age and over the duration of breastfeeding. Methods: Single Centre observational prospective longitudinal cohort study. Data were collected from medical records, and medical history. The analysis of multiple linear and mixed models was involved. Findings: 20% of females were overweight, while 13% were obese before the pregnancy. An overall model, including gender and smoking, indicated a significant impact of pBMI category on a child's birth mass (p = 0.01). The GWG category affected a child's birth weight (p = 0.018, Effect size 0.41). pBMI did not affect the breastfeeding duration. Conclusion: pBMI and GWG correlate with birth weight and weight in neonatal period, however they become insignificant in later childhood. Weight assessment methods among children aged up to two years of age require standardization. Maternal weight before the pregnancy nor the weight gain during the pregnancy do not influence the length of breastfeeding. The biggest limitation was the small sample size and the failure to account for weight gain per trimester of pregnancy. Further research on a larger population should be continued.